The Influence of Work Environment, Job Satisfaction and Motivation on Employee Performance at PT Khurnia Sawit Jaya Kabupaten Labuhan Batu Sumatera Utara - Surya Ananta Febrianti; Kholilul Kholik; Yana Diana (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of Work Environment, Job Satisfaction, and Motivation on Employee Performance at PT. Khurnia Sawit Jaya, South Labuhan Batu Regency, North Sumatra. The type of research used is associative with a quantitative approach, where data were obtained through distributing questionnaires to 92 respondents who are company employees. Data analysis was carried out using multiple linear regression with the help of the SPSS program version 24.0. The results of the study indicate that partially the work environment, job satisfaction, and motivation each have a positive and significant influence. Simultaneously, these three variables have a significant effect on employee performance with an F count of 86.577 and a significance of 0.000. The coefficient of determination (R²) of 0.747 indicates that 74.7% of employee performance variations can be explained by the work environment, job satisfaction, and motivation, while the remaining 25.3% is influenced by other factors outside this study. Thus, it can be concluded that improving the conducive work environment, high job satisfaction, and strong motivation will have a positive impact on improving employee performance at PT. Khurnia Sawit Jaya.